Integrated Radar and Missile System with Poisson-Prioritized Threat Management and PPN Guidance for Countering Multiple UAV Threats - Hage, Giselle; Santoso, Ari; Sahal, Mochammad (Universitas Muhammadiyah Yogyakarta, 2025)
In military defense, critical infrastructure protection, and border and maritime surveillance, radar detection plays a critical role in neutralizing threats, since slight delays in detection can enable hostile UAVs to breach defenses and target critical objectives. This research proposes an air defense systems, consists of integrated radar and missile system, to detect and neutralize aerial threats. The radar detects UAVs, tracks their trajectories, and prioritizes threats according to the distance of UAVs within its detection range, incorporating Poisson-distributed probability to dynamically allocate missile resources, allowing the systems to cover broader threat zones, which is crucial for the real-time interception of multiple UAVs. Each UAV is equipped with a state feedback controller for accurate navigation, while the missile system consistently enhancing its trajectory to accurately track and intercept threats under PPN guidance. Simulated experiments indicate that the proposed system intercepted the aerial threats within its operational range and time constraints in various battlefield scenarios. The system’s effect within its operational radius has also been evaluated in an experiment designed to counter a swarm of 6 UAVs flies in a predefined formation. In this scenario, the air defense system successfully launched a missile towards UAV swarms that neutralized 83.33% of total identified threats. The proposed system can be an alternative air defense systems to confront UAV threats in battlefield situations, with potential application in disaster management, search and rescue, and early warning system.